(untitled) (Research, Society and Development, 2021)
Due to the ability to germinate, grow and reproduce under adverse conditions, such as in situations of water deficit, salinity, acidic or alkaline soils and unsuitable temperatures, weeds have been one of the most difficult phytosanitary problems to be controlled in agricultural areas, which can result in damages that can reach high levels of crop losses. The aim of this study was to evaluate the efficiency of isolated application of Glyphosate, and associated with the herbicides Chlorimuron, Imazethapyr, Lactofen and Flumioxazin in the control of Ipomoea grandifoli. For this, an experiment was carried out in the greenhouse of the experimental field at UNIVAG – Centro Universitário de Várzea Grande. The experimental design adopted was a randomized block, with six treatments (Glyphosate, Glyphosate + Imazethapyr, Glyphosate + Clorimoron, Glyphosate + Flumioxazin, Glyphosate + Lactofen and control) and four replications totaling 24 plots. To determine the results, phytotoxicity evaluations were carried out based on a visual scale of notes at 7, 14 and 21 days after application. Among the herbicides tested, the treatments with Glyphosate + Flumioxazin and Glyphosate + Lactofen produced the best result (100% control), whereas the treatments using Glyphosate alone, Glyphosate + Imezethapyr and Glyphosate + Clorimuron showed inferior control to control the viola string.